Dangers in the Practice of Defensive Medicine in Hemostasis Testing for Investigation of Bleeding or Thrombosis: Part I—Routine Coagulation Testing - Lippi, Giuseppe; Favaloro, Emmanuel J.; Franchini, Massimo (Seminars in Thrombosis and Hemostasis, 2014)
Defensive medicine is a term conventionally used for defining the medical (mal)practice of ordering medically questionable diagnostic testing, procedures, or visits, or to avoid high-risk patients or procedures. The practice of defensive medicine may primarily be aimed to reduce exposure to malpractice liability, to avoid patient criticism regarding “medical inaction,” or to avoid “missing” some otherwise potential identifiable defect(s). Although the precise impact of defensive medicine in the field of laboratory testing is difficult to estimate from the current literature, the overuse or inappropriate use of laboratory resources ranges from 23 to 67%, and a large part of this can be attributed to medical liability concerns, with apparently little clinical awareness of the adverse consequences that may be associated with this practice. Essentially, performing inappropriate testing remarkably increases the risk of obtaining false-positive results due to statistical, preanalytical, and analytical reasons, thus triggering further and potentially even more invasive follow-up testing, inappropriate patient management, along with incremental increases of expenditure due to misuse of health care resources. As routine coagulation testing is commonly performed for the screening of patients with bleeding or thrombotic disorders, either a false-negative or a false-positive result may significantly impact on clinical outcomes and health care resources. The aim of this article is to describe the leading causes of physiological, pathological, therapeutic, and spurious variations of the prothrombin time, activated partial thromboplastin time, and D-dimer, as well as the potential clinical consequences emerging from the generation of false-negative and false-positive results with these tests.
Keywords: defensive medicine; inappropriateness; prothrombin time; activated partial thromboplastin time; D-dimer